Kesadaran Hukum Lingkungan Sebagai Modal Sosial Strategis Pada Aktivitas Penambangan Timah Rakyat di Kepulauan Bangka Belitung - Dwi Haryadi; Ibrahim Ibrahim; Darwance Darwance (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
Since ancient times, the Bangka Belitung Islands have been known as one of the world’s largest tin producers. Mining has taken place massively since tin is no longer a strategic commodity, marked by the issuance of several policies that grant permits to anyone to mine tin. Mining, which was originally mostly carried out on land, over time and needed in the economic aspect, has also been carried out at sea. As a result, mining, mostly carried out without permits, impacts environmental damage and other legal and social aspects. In fact, from a regulatory standpoint, the government has issued laws and regulations that serve as references in environmental management, including its relation to the mining sector. This study aims to determine awareness of environmental law in unconventional tin mining activities in the Bangka Belitung Islands. Judging from its type, this research is analytical descriptive research, describing an object through which the data obtained is processed and analyzed to conclude. The research was conducted in all regencies/municipalities in the Bangka Belitung Islands. From the research that has been done, the result is that even though they know, the fact is that most of the mining is carried out without permits, plus there has never been, and there has been no socialization regarding tin mining permits. In addition, most of them also know that their mining activities damage the environment and admit that mining activities damage the habitat of living things. This means that, based on the theories and concepts used, miners are more towards ecocentrism because they make nature an object, not ecocentrism, which pays attention to environmental sustainability.